Tax Compliance Transformation: The Role of E-Tax System and Money Ethics Through Taxpayer Behavioral Intentions - Nurhapsari, Risma; Rohmania, Aftuqa Sholikatur; Sholihah, Erlinda (E-Jurnal Akuntansi; Vol 34 No 12 (2024)DO - 10.24843/EJA.2024.v34.i12.p11, 2024)
This study examines the impact of attitudes toward the e-tax system, e-tax system adoption, and money ethics on tax compliance, with taxpayer behavioral intentions serving as a mediating variable. A mixed-method approach, integrating both qualitative and quantitative methodologies, was employed. Data were collected through semi-structured interviews and a survey of 200 culinary MSME respondents in Central Java. The analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that taxpayer behavioral intentions significantly and positively influence tax compliance. However, attitudes toward the e-tax system exhibit a significant negative effect. In contrast, e-tax system adoption positively and significantly impacts tax compliance, while money ethics, though negatively related, has an insignificant effect. Additionally, attitudes toward the e-tax system negatively affect taxpayer behavioral intentions, whereas e-tax system adoption has a significant positive impact. Money ethics again show a negative but statistically insignificant effect on behavioral intentions. Notably, taxpayer behavioral intentions mediate only the relationship between e-tax system adoption and tax compliance. This study provides valuable insights for tax authorities, emphasizing the need for policies that enhance MSME tax compliance by addressing behavioral barriers and optimizing the adoption of digital tax systems.